H2O2‐induced microvessel barrier dysfunction: the interplay between reactive oxygen species, nitric oxide, and peroxynitrite - Xueping Zhou (Physiological Reports, 2019)
Abstract Elevated H2O2 is implicated in many cardiovascular diseases. We previously demonstrated that H2O2‐induced endothelial nitric oxide synthase (eNOS) activation and excessive NO production contribute to vascular cell injury and increases in microvessel permeability. However, the mechanisms of excessive NO‐mediated vascular injury and hyperpermeability remain unknown. This study aims to examine the functional role of NO‐derived peroxynitrite (ONOO−) in H2O2‐induced vascular barrier dysfunction by elucidating the interrelationships between H2O2‐induced NO, superoxide, ONOO−, and changes in endothelial [Ca2+]i and microvessel permeability. Experiments were conducted on intact rat mesenteric venules. Microvessel permeability was determined by measuring hydraulic conductivity (Lp). Endothelial [Ca2+]i, NO, and O2− were assessed with fluorescence imaging. Perfusion of vessels with H2O2 (10 µmol/L) induced marked productions of NO and O2−, resulting in extensive protein tyrosine nitration, a biomarker of ONOO−. The formation of ONOO− was abolished by inhibition of NOS with NG‐Methyl‐L‐arginine. Blocking NO production or scavenging ONOO− by uric acid prevented H2O2‐induced increases in endothelial [Ca2+]i and Lp. Additionally, the application of exogenous ONOO− to microvessels induced delayed and progressive increases in endothelial [Ca2+]i and microvessel Lp, a pattern similar to that observed in H2O2‐perfused vessels. Importantly, ONOO− caused further activation of eNOS with amplified NO production. We conclude that the augmentation of NO‐derived ONOO− is essential for H2O2‐induced endothelial Ca2+ overload and progressively increased microvessel permeability, which is achieved by self‐promoted amplifications of NO‐dependent signaling cascades. This novel mechanism provides new insight into the reactive oxygen and/or reactive nitrogen species‐mediated vascular dysfunction in cardiovascular diseases.